Rancang Bangun Smart Monitoring System di Laboratorium Elektro Universitas Teknologi Sumbawa Berbasis Esp32 dan Blynk - Arief Taradhyatama; Paris Ali Topan; Masyitah Aulia; Nova Aryanto (Jurnal Altron, 2022)
The smart monitoring system is an Internet of Things (IoT) innovation, where the use of all daily electronic devices can be optimized due to the integration of technology in the versatile 4.0 era. In terms of smart monitoring systems, the internet of things comes with being able to manage tools that are commonly found in most homes. The application of this smart monitoring system uses ESP32 as a microcontroller and Blynk IoT as a controlling or monitoring tool. This system consists of controlling the current by relay, then the relay can be controlled automatically or manually. Based on the results of testing the smart monitoring system in the Electrical Laboratory room, the control of lights and monitoring of electricity usage based on Blynk must always be connected to the internet.